Efficacy, safety, and immunogenicity of SARS-CoV-2 mRNA vaccine (Omicron BA.5) LVRNA012: a randomized, double-blind, placebo-controlled phase 3 trial - Zhou, Huan; Zheng, Hui; Peng, Yucai; Su, Yue; Yu, Xuya; Wang, Weixiao; Li, Simin; Ding, Yuzhou; Jiao, Shiping; Wang, Ying; Zhu, Xingyu; Luo, Liping; et al. (Frontiers in Immunology, 2024)
Background: We aimed to evaluate the efficacy, safety, and immunogenicity of a SARS-CoV-2 mRNA vaccine (Omicron BA.5) LVRNA012 given as the booster in immunized but SARS-CoV-2 infection-free adults in China. Methods: This is a single-center, randomized, double-blind, placebo-controlled phase 3 clinical trial enrolling healthy adult participants (≥18 years) who had completed two or three doses of inactivated COVID-19 vaccines at least 6 months before, in Bengbu, Anhui province, China. Eligible participants were randomly assigned (1:1) to receive a booster intramuscular vaccination with an LVRNA012 vaccine (100ug) or placebo. The primary endpoint was the protective efficacy of a booster dose of the LVRNA012 vaccine or placebo against symptomatic COVID-19 of any severity 14 days after vaccination. Laboratory-confirmed COVID-19 infections were identified from 14 days to 180 days after intervention, with active surveillance for symptomatic illness 8 times per month between 7 to 90 days and at least once per month between 90 to 180 days after intervention. Results: 2615 participants were recruited and randomly assigned in a 1:1 ratio to either the vaccine group (1308) or the placebo group (1307). A total of 141 individuals (46 in the LVRNA012 group and 95 in the placebo group) developed symptomatic COVID-19 infection 14 days after the booster immunization, showing a vaccine efficacy of 51.9% (95% CI, 31.3% to 66.4%). Most infections were detected 90 days after intervention during a period when XBB was prevalent in the community. Adverse reactions were reported by 64% of participants after the LVRNA012 vaccination, but most of them were mild or moderate. The booster vaccination with the LVRNA012 mRNA vaccine could significantly enhance neutralizing antibody titers against the Omicron variant XBB.1.5 (GMT 132.3 [99.8, 175.4]) than did those in the placebo group (GMT 12.5 [8.4, 18.7]) at day 14 for the previously immunized individuals. Conclusions: The LVRNA012 mRNA vaccine is immunogenic, and shows robust efficacy in preventing COVID-19 during the omicron-predominate period.